Vocal Behavior in Spotted Seals (Phoca largha) and Implications for Passive Acoustic Monitoring - Sills, Jillian M.; Reichmuth, Colleen (Frontiers in Remote Sensing, 2022)
Passive acoustic methods enable remote monitoring of marine species and habitats. These methods can be applied to investigate distribution and abundance of populations, to evaluate behavioral and physiological states of individuals, and to inform management efforts for animals that live in hard-to-reach places. Spotted seals (Phoca largha) inhabit high-latitude, light-limited sub-Arctic and Arctic waters and move seasonally with unstable sea ice. They are high trophic level predators vulnerable to changing conditions associated with environmental warming. At present, an incomplete characterization of the spotted seal vocal repertoire limits our ability to monitor this species acoustically. Captive studies can inform passive acoustic efforts by describing fundamental features of species-typical vocalizations emitted by known individuals. These features include acoustic parameters as well as developmental, seasonal, and sex-specific patterns in vocal behavior. Here, several male spotted seals were studied in captivity from age 6 months through adulthood (10 y). Vocal behavior was scored daily and opportunistically recorded. The production of underwater calls emerged during sexual maturation, at age 4. To evaluate vocal repertoire and fine-scale temporal patterns of sound production in adult seals, an underwater acoustic recorder was continuously deployed with two seals at age 7 years. The spotted seals produced at least eight distinctive underwater call types with dominant energy below 1 kHz. The amplitude of the most common vocalization was ~140 dB re 1 μPa (sound pressure level at 1 m). There was a marked peak in vocal activity in springtime, prior to onset of the annual molt. This period coincided with increased aggressive behavior, presence of a notable musky odor, and urogenital swelling indicative of heightened reproductive status. These results from developing male spotted seals reared in human care confirm the production of recognizable, stereotypic underwater calls associated with the breeding season. Description of vocal behavior improves knowledge of this species’ biology, and informs the potential use of autonomous acoustic recorders to track the presence and movements of free-ranging spotted seals in remote habitats.